Pediatric Liver Transplantation Secondary to Hepatoblastoma without the use of a Kehr’s T tube: A Case Report - Saldaña-Ruiz, Mauricio Alejandro; Rendón-Saldivar, Mauricio Linnery; Sánchez-Maldonado, Héctor Fernando; Álvarez-Treviño, Guillermo Alberto; Ortiz-Alonso, Federico; Azpilcueta-García, Jaime (International Journal of Medical Students, 2023)
BACKGROUND: Hepatoblastoma is a common primary malignant tumor in the pediatric population, it has a PRETEXT staging depending on the degree of hepatic involvement, in this stage III central and IV are indications for transplantation. At the same time, it has sought to reduce the occurrence of post-transplant complications by not using a Kehr’s T tube during the choledocho – choledochostomy, obtaining interesting results. THE CASE A 16-month-old woman diagnosed with PRETEXT IV hepatoblastoma, who received four cycles of chemotherapy (CTX) with cisplatin plus doxorubicin, adding two cycles of ICE, before her next cycle she was informed of the availability of a cadaveric liver graft, for this reason she received a liver transplant and during surgery it was decided not to use a Kehr’s T tube. She remained stable on her first post-transplant day. On her second day, a collection in the hepatic hilum was evidenced by control Doppler ultrasound (US), placing two Blake drains. The following four days she had a favorable evolution, being discharged to transplantation floor with a downward trend of liver enzymes, where she continued with the same trend and US Doppler with adequate flows, leaving on day 19 post-transplant. One month later, she received two cycles of adjuvant CTX with CAV scheme. Currently, graft is functional and free of disease. CONCLUSION: Liver transplantation is the treatment of choice, reaching a survival rate of over 80% at five years post-transplantation. Furthermore, even though the technique of choice is hepaticojejunostomy, it was decided to perform a choledocho – choledochostomy without a Kehr’s T tube, without the development of complications, which is consistent with results in the literature that show that the use of this technique prevents the appearance of complications in up to half of the cases, compared to when the tube is used. Also, adjuvant QT contributes to a better evolution and to obtaining a negative tumor marker, as was the case of the patient.